Calretinin-Periglomerular Interneurons in Mice Olfactory Bulb: Cells of Few Words - Fogli Iseppe, Alex; Pignatelli, Angela; Belluzzi, Ottorino (Frontiers in Cellular Neuroscience, 2016)
Within the olfactory bulb (OB), periglomerular (PG) cells consist of various types of interneurons, generally classified by their chemical properties such as neurotransmitter and calcium binding proteins. Calretinin (CR) characterizes morphologically and functionally the more numerous and one of the less known subpopulation of PG cells in the OB. Using of transgenic mice expressing eGFP under the CR promoter, we have tried to obtain the first functional characterization of these cells. Electrophysiological recordings were made in these cells using the patch-clamp technique in thin slices. Using ion substitution methods and specific blockers, we dissected the main voltage-dependent conductances present, obtaining a complete kinetic description for each of them. The more peculiar property of these cells from the electrophysiological point of view is the presence only of a single K-current, the IA - there is no trace of delayed rectifier or of Ca-dependent K-current. Other currents identified, isolated and fully characterised are two inward currents, a fast sodium current and a small L-type calcium current, and an inward rectifier, h-type cationic current. As a consequence of the peculiar complement of voltage-dependent conductances present in these cells, and in particular the absence of delayed-rectifier potassium currents, under the functional point of view these cells present two interesting properties. First, in response to prolonged depolarisations, after the inactivation of the A-current, these cells behave as a purely ohmic elements, showing no outward rectification. Second, the CR cells studied can respond only with a single action potential to excitatory inputs; since they send inhibitory synapses to projection neurones, they seem to be designed to inhibit responses of the main neurones to isolated, random excitatory signals, losing their vetoing effect for more structured, repetitive excitatory signals, as result from odour detection. We propose that a possible role for these rather untalkative interneurons in the intense exchange of messages within the olfactory bulb might be that of improving the signal-to-noise ratio in the first stages of the olfactory information processing.